Pelatihan Kebidanan Lanjutan pada Bidan terhadap Penurunan Angka Kematian Ibu - Arif Setiawan; Djazuly Chalidyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of advanced midwifery training in reducing maternal mortality. The method used is using training, discussion, and demonstration. This type of research is descriptive using secondary data on birth data and maternal mortality. Continuous training carried out during 2016 and 2017 was proven to reduce maternal mortality in Surabaya. The MMR in 10 sub-districts trained in 2015 was 113.7 per 100,000 births; this figure is still above the MDGs standard. After the MMR training was carried out in 10 sub-districts that received training in 2016, it was 81.8 per 100,000 births, and in 2017 it was 66.5 per 100,000 births. The results of the simple T-test showed a significant reduction in maternal mortality with p=0.04 (p<0.05). In conclusion, continuous training for midwives reduces maternal mortality in Surabaya. Keywords: Midwifery Maternal Mortality Rate, Midwifery Training